2016
DOI: 10.7860/jcdr/2016/22412.8843
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale 7436-bp Deletions in Human Sperm Mitochondrial DNA with Spermatozoa Dysfunction and Male Infertility

Abstract: IntrOductIOnSperm motility is essential factor of fertile men. During fertilization, sperm cells require large amount of energy for their movement of flagella and active functioning. Nearly, 100 mitochondria are present in the midpiece of every mature human spermatozoon to provide energy quickly and effectively for sperm motility [1]. The oxidative phosphorylation of mitochondria generates energy in the form of ATP for flagellar movement of spermatozoa. In mitochondria, Reactive Oxygen Species (ROS) is generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…They indicated that 7436‐bp deletion of mtDNA is associated with abnormal sperm motility, so, the nonmotile spermatozoa in 40% percoll fractions showed more mtDNA deletions (7.2%) than the motile spermatozoa in 80% percoll fraction (2.7%). Other studies, in consistence with our results, confirmed the association of large‐scale 7436‐bp sperm mtDNA deletions with poor sperm motility in asthenozoospermia and OAT patients, but the frequencies of 7436‐bp deletions are less than that of 4977‐bp “common” deletions . In IVF/intracytoplasmic sperm injection (ICSI) cases, spermatozoa with a significant load of “common” mtDNA 4977‐bp deletion do not produce enough energy for their movement and thus reduce male fertility, mainly affecting oocyte fertilization .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…They indicated that 7436‐bp deletion of mtDNA is associated with abnormal sperm motility, so, the nonmotile spermatozoa in 40% percoll fractions showed more mtDNA deletions (7.2%) than the motile spermatozoa in 80% percoll fraction (2.7%). Other studies, in consistence with our results, confirmed the association of large‐scale 7436‐bp sperm mtDNA deletions with poor sperm motility in asthenozoospermia and OAT patients, but the frequencies of 7436‐bp deletions are less than that of 4977‐bp “common” deletions . In IVF/intracytoplasmic sperm injection (ICSI) cases, spermatozoa with a significant load of “common” mtDNA 4977‐bp deletion do not produce enough energy for their movement and thus reduce male fertility, mainly affecting oocyte fertilization .…”
Section: Discussionsupporting
confidence: 91%
“…In general, the frequency of 7436‐bp deletions in sperm mtDNA was the lowest than two other deletions (4.8 and 4.9 Kb) in both infertile and control groups. Interestingly, Ambulkar et al and Rani et al could not find deletion of 7436 bp in normospermic subjects. St. John et al showed the persistence of multiple mtDNA deletions in both normozoospermic and oligoasthenoteratozoospermic (OAT) men.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, mtDNA 4977 has been recorded in the spermatozoa of infertile males with asthenozoospermia and oligoasthenozoospermia [148,149]. An alternative large-scale mtDNA deletion comprising 7436 bp (mtDNA 7436 ) has also been reported in low-motility human spermatozoa [150]. In addition to the genes excised by mtDNA 4977 , mtDNA 7436 also eliminates genes encoding subunit 6 of Complex I (ND6) and cytochrome b from the mtDNA genome (see Figure 3).…”
Section: Sperm Dna Modificationsmentioning
confidence: 99%